Risk factors for high bulk milk somatic cell counts in dairy herds from Campos das Vertentes region, Minas Gerais State, Brazil: a case-control study - Geraldo M. Costa; Alan A. Mesquita; Christiane M.B.M. Rocha; Fabio R.P. Bruhn; Rafaella S. Andrade; Dircéia A.C. Custódio; Mirian S. Braz; Sandra M. Pinto (Pesquisa Veterinária Brasileira, 2019)
ABSTRACT: High bulk milk somatic cell counts (BMSCC) are indicative of failures related to the control of mastitis in the herd, which compromises the quality of the milk and generates great losses for the producers and for the industry. A case-control study was carried out in dairy herds in the Campos das Vertentes region, Minas Gerais State, Brazil, in order to contribute to the knowledge of the risk factors involved with elevated BMSCC. The study involved 46 dairy herds, of which 30 were considered cases (BMSCC ≥700,000 cells/mL of milk) and 16 control farms (BMSCC ≤200,000 cells/mL of milk). Sixteen qualitative variables and four quantitative variables were analyzed. The results showed that the risk factors for BMSCC ≥700,000 cells/mL were the presence of Staphylococcus aureus and Streptococcus agalactiae pathogens in bulk milk, non-use of pre and post-dipping, non-use of disposable paper towel for drying of mammary glands, non-monitoring of mastitis in the herd by means of California Mastitis Test (CMT) or individual somatic cell counts (SCC), non-implementation of the milking line and therapy of dry cows and failures in hygiene of teats and udders before milking. Moderate correlations were also observed between the elevation of BMSCC and counts of S. aureus and BMSCC and counts S. agalactiae in bulk milk, and a moderate correlation between S. aureus and S. agalactiae counts in bulk milk. Failures with regard to the maintenance and use of milking equipment, including manual pressure application in milking assemblies, unregulated milking vacuum pressure, and vacuum loss during milking, and maintenance failures of the milking machine and bulk milk tank were also pointed out as important risk factors of BMSCC elevation. The results of this study provided subsidies for the elaboration of more effective programs for mastitis control and improvement of raw milk quality, reducing the losses caused by the disease to producers and industry.